(untitled) (CIPEEX, 2025)
Introduction: The gut is connected to the central nervous system (CNS) and influences brain function through nerves, blood circulation, and lymphatic pathways. The gut microbiota, a complex ecosystem of trillions of microorganisms, plays a vital role in brain health. The balance of the gut microbiota is critical for mental and physical health, involving the gut-brain microbiota axis (BGMA). Objective: Review clinical studies on the relationship between the gut microbiome and mental health conditions. Methodology: An integrative literature review of studies published in the last five years, using PUBMED and MEDLINE databases with the descriptors "gut microbiome" and "mental health." Discussion and Results: Research on psychobiotics shows that the gut microbiota influences neurotransmitter synthesis and mood regulation. Gut dysbiosis, an imbalance in the microbiota, affects mental health, with changes in bacteria profiles associated with neurological disorders. Healthy microbiota, dominated by Firmicutes and Bacteroidetes, plays a role in inflammation regulation and intestinal barrier maintenance. Patients with depression exhibit distinct bacterial profiles compared to healthy individuals. Conclusion: The gut-brain microbiota axis is critical for mental health. Dysbiosis is linked to psychiatric disorders but can be mitigated by microbiota transplantation. Maintaining gut microbiota balance offers new perspectives for treating psychiatric conditions.